A kind of high-strength thermal conductive silica gel and preparation method thereof

By using the hindered phenol structure and benzophenone structure in the additives in thermally conductive silica gel, its anti-aging performance is enhanced, and the problem of poor performance stability of thermally conductive silica gel in long-term use is solved, and the stability of high strength and high thermal conductivity is achieved, which extends the service life and ensures the stable operation of electronic equipment.

CN118994912BActive Publication Date: 2025-04-25SHENZHEN GUANGXU TECH APPL NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411279062.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-04-25
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

It is difficult for existing thermal conductivity silicone to maintain stability in thermal conductivity and physical properties during long-term use, and it has poor adaptability to complex and variable usage environments.

Method used

A high-strength thermally conductive silicone is used to prepare a high-strength thermally conductive silicone, including a combination of liquid silicone rubber, silicone oil, crosslinking agent, inhibitor, additive and thermally conductive filler. Through the synergistic effect of the hindered phenol structure and benzophenone structure in the additive, the anti-ultraviolet aging and thermally oxygen aging properties of the silicone are enhanced.

Benefits of technology

The high intensity and high thermal conductivity of thermally conductive silicone under environmental factors such as temperature changes, humidity changes, and ultraviolet radiation are achieved, which extends the service life and ensures the stable operation of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041089200000021
    Figure BDA0005041089200000021
  • Figure BDA0005041089200000031
    Figure BDA0005041089200000031
  • Figure BDA0005041089200000032
    Figure BDA0005041089200000032
Patent Text Reader

Abstract

The invention discloses a high-strength thermally conductive silicone and a preparation method thereof, and belongs to the technical field of thermally conductive silicone. The high-strength thermally conductive silicone comprises the following raw materials by weight: 15-25 parts of liquid silicone rubber, 30-45 parts of silicone oil, 2-5 parts of cross-linking agent, 0.05-0.15 parts of inhibitor, 1-3 parts of auxiliary agent, 250-350 parts of thermally conductive filler, and 0.3-0.6 parts of catalyst; the auxiliary agent and the silicone oil are cross-linked with each other, so the auxiliary agent can be stably present in the thermally conductive silicone, and the hindered phenol structure and the benzophenone structure in the auxiliary agent can also give full play to the synergistic effect, giving the thermally conductive silicone excellent resistance to ultraviolet aging and heat-oxidation aging, and then the thermally conductive silicone of the present invention can resist the influence of environmental factors such as temperature change, humidity change, ultraviolet radiation, etc., and always maintain high strength and high thermal conductivity, so that the service life of the thermally conductive adhesive is extended, and the stable operation of the electronic equipment is also guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermally conductive silicone rubber, and in particular relates to a high-strength thermally conductive silicone rubber and a preparation method thereof. Background Art

[0002] In the face of crises such as global warming, energy conservation and emission reduction have become the top priority in solving the problem, and more new energy vehicles have emerged. As the core power source of new energy vehicles, how to efficiently and safely conduct and dissipate heat during operation has become a core issue in new energy vehicle technology. The silicone material wrapped on the outside directly determines the optimization direction of the relevant performance of new energy vehicle batteries.

[0003] As a high-performance heat dissipation material, the stability and durability of thermal conductive silicone's high strength, high thermal conductivity and other properties are crucial to the normal operation of electronic equipment. Therefore, thermal conductive silicone must have excellent anti-aging properties to ensure that its thermal conductivity and physical properties remain stable during long-term use, and adapt to various complex and changing use environments. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-strength thermal conductive silica gel and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength thermally conductive silica gel comprises the following raw materials in parts by weight: 15-25 parts of liquid silicone rubber, 30-45 parts of silicone oil, 2-5 parts of a cross-linking agent, 0.05-0.15 parts of an inhibitor, 1-3 parts of an auxiliary agent, 250-350 parts of a thermally conductive filler, and 0.3-0.6 parts of a catalyst.

[0007] Furthermore, the silicone oil is prepared by compounding methyl silicone oil and vinyl silicone oil in a mass ratio of (4-9):1.

[0008] Furthermore, the cross-linking agent is hydrogen-based silicone oil.

[0009] Hydrogen-based silicone oil can enhance the intermolecular force and strengthen the cross-linking with the main body through hydrogen bonding, so that the thermal conductive silicone can obtain good stability and electrolyte resistance.

[0010] Furthermore, the inhibitor is one or more of 1-ethynyl-1-cyclohexanol, 2-vinyl isopropanol, 4-pentyn-1-ol, and acetic acid-4-ynol.

[0011] Furthermore, the auxiliary agent is prepared by the following steps:

[0012] S1. Add 2,4-dihydroxybenzophenone, pyridine and anhydrous ethanol to a dry four-necked flask under nitrogen protection, stir to dissolve, then slowly add 3-chloropropyltrimethoxysilane, heat to 110°C after addition, keep warm for 4 hours, cool to room temperature after the reaction, concentrate, wash with anhydrous ethanol by centrifugation 3 times, concentrate again, recrystallize the obtained crude product with anhydrous ethanol, filter and dry at 80°C for 12 hours to obtain intermediate 1; the amount ratio of 2,4-dihydroxybenzophenone, 3-chloropropyltrimethoxysilane, pyridine and anhydrous ethanol is 17.1g:15.5mL:7.8mL:180mL;

[0013] Pyridine is used as an acid binding agent to control the molar ratio of 2,4-dihydroxybenzophenone and 3-chloropropyltrimethoxysilane to be 1:1.05-1.1, and the -OH of 2,4-dihydroxybenzophenone and the -Cl of 3-chloropropyltrimethoxysilane undergo a substitution reaction. The reaction process is as follows:

[0014]

[0015] S2. Under nitrogen protection, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, glycerol and DMF (N,N-dimethylformamide) were added to a dry three-necked flask, and concentrated sulfuric acid was slowly added after sufficient stirring. The temperature was raised to 110°C for reaction for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and sodium carbonate solution was added for neutralization. After shaking, the mixture was allowed to stand for stratification. The organic phase was dried over anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure. The filtrate was purified by column chromatography (a mixed solvent of cyclohexane and ethyl acetate was selected as the eluent, and the volume ratio of cyclohexane and ethyl acetate was 1:1), and the eluent was removed by distillation under reduced pressure to obtain intermediate 2; the amount ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, glycerol, concentrated sulfuric acid and DMF was 29.9 g:3.7 mL:1.1 mL:200 mL;

[0016] Under concentrated sulfuric acid and heating conditions, the molar ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and glycerol is controlled to be 2.1-2.2:1, then the -COOH of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and the -OH of glycerol undergo esterification reaction, and the reaction process is as follows:

[0017]

[0018] S3. Blow nitrogen gas into a dry three-necked flask for 30 minutes to exclude air and moisture, add intermediate 2, tetraisopropyl titanate and DMF into the flask, stir to dissolve, then slowly add a mixed solution of intermediate 1 and DMF, heat to 90°C and react for 24 hours after the addition is complete, cool to room temperature after the reaction is completed, distill under reduced pressure, wash with anhydrous ethanol for 3 times, dry at 80°C for 12 hours to obtain an auxiliary agent; the amount ratio of intermediate 1, intermediate 2, tetraisopropyl titanate and DMF is 13g:18.4g:0.026g:180mL.

[0019] Under the catalytic action of tetraisopropyl titanate, the molar ratio of intermediate 1 to intermediate 2 is controlled to be 1.1-1.2:1, and the silaneoxy group of intermediate 1 and the hydroxyl group of intermediate 2 undergo the following chemical reaction. The reaction process is as follows:

[0020]

[0021] The additive contains hindered phenol structure, which can effectively terminate the transmission and growth of free radical chains in the oxidation process and protect the polymer from the effects of thermal oxidation aging. In addition, the hindered phenol structure can also react with hydrogen peroxide (intermediate product of the oxidation process) to convert it into water and alcohol, further inhibiting the oxidation process. This reaction not only helps to reduce the damage of oxidative stress to the polymer, but also enhances the stability and durability of the material. Under certain conditions, the phenol oxygen free radical generated by the reaction of the hindered phenol structure with free radicals can react with another hindered phenol molecule to regenerate hindered phenol and a stable non-free radical molecule. This process allows the hindered phenol to regenerate and continue to play an antioxidant role, thereby delaying the thermal oxidation aging process of the material and reducing the color change, mechanical property degradation and other physical and chemical property degradation caused by oxidation. The additive also contains benzophenone structure, which can absorb high-energy ultraviolet light and convert light energy into heat energy for release, or into other harmless energy forms for release, playing the role of ultraviolet absorption.

[0022] The auxiliary agent contains silaneoxy groups, which can form chemical bonds with silaneoxy groups in silicone oil to form crosslinks. Therefore, the auxiliary agent can stably exist in the thermally conductive silica gel. The hindered phenol structure and the benzophenone structure in the auxiliary agent can fully exert their synergistic effect, giving the thermally conductive silica gel excellent resistance to ultraviolet aging and thermal-oxidative aging. Therefore, the thermally conductive silica gel of the present invention can resist the influence of environmental factors such as temperature changes, humidity changes, and ultraviolet radiation, and always maintain high strength and high thermal conductivity, thereby extending the service life of the thermally conductive adhesive and ensuring the stable operation of electronic equipment.

[0023] Furthermore, the thermally conductive filler is one or more of aluminum oxide, aluminum hydroxide, magnesium oxide, silicon dioxide, and boron nitride.

[0024] Furthermore, the catalyst is a platinum catalyst.

[0025] A method for preparing high-strength thermally conductive silica gel comprises the following steps:

[0026] Weigh each raw material by weight, premix the liquid silicone rubber, silicone oil and crosslinking agent, add the thermal conductive filler and knead them, add the auxiliary agent, inhibitor and catalyst in sequence after kneading evenly, knead and cure, and obtain high-strength thermal conductive silicone.

[0027] The beneficial effects of the present invention are as follows: the auxiliary agent and the silicone oil are cross-linked with each other, so the auxiliary agent can stably exist in the thermally conductive silica gel, and the hindered phenol structure and the benzophenone structure in the auxiliary agent can also give full play to the synergistic effect, giving the thermally conductive silica gel excellent resistance to ultraviolet aging and thermal-oxidative aging. Furthermore, the thermally conductive silica gel of the present invention can resist the influence of environmental factors such as temperature changes, humidity changes, and ultraviolet radiation, and always maintain high strength and high thermal conductivity, so that the service life of the thermally conductive adhesive is extended, and the stable operation of electronic equipment is also guaranteed. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] Preparation of auxiliary agent, the specific steps are as follows:

[0031] S1. Add 17.1 g of 2,4-dihydroxybenzophenone, 7.8 mL of pyridine and 180 mL of anhydrous ethanol to a 500 mL dry four-necked flask under nitrogen protection, stir to dissolve, then slowly add 15.5 mL of 3-chloropropyltrimethoxysilane, heat to 110°C after the addition, keep warm for 4 hours, cool to room temperature after the reaction, concentrate, wash with anhydrous ethanol by centrifugation 3 times, concentrate again, recrystallize the obtained crude product with anhydrous ethanol, filter with suction, and dry at 80°C for 12 hours to obtain intermediate 1;

[0032] S2, under nitrogen protection, add 29.9g 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3.7mL glycerol and 200mL DMF into a 500mL dry three-necked flask, stir thoroughly and then slowly add 1.1mL concentrated sulfuric acid, heat to 110°C and react for 3h, cool to room temperature after the reaction, add sodium carbonate solution to neutralize, shake and stand for stratification, take the organic phase and dry it with anhydrous magnesium sulfate, filter, distill the filtrate under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of cyclohexane and ethyl acetate, the volume ratio of cyclohexane and ethyl acetate is 1:1), and then distill the eluent under reduced pressure to obtain intermediate 2;

[0033] S3. Blow nitrogen gas into a 500mL dry three-necked flask for 30 minutes to exclude air and moisture, add 18.4g of intermediate 2, 0.026g of tetraisopropyl titanate and 140mL of DMF into the flask, stir to dissolve, then slowly add a mixed solution of 13g of intermediate 1 and 40mL of DMF, heat to 90°C after the addition is complete, react for 24 hours, cool to room temperature after the reaction is completed, distill under reduced pressure, wash with anhydrous ethanol 3 times, and dry at 80°C for 12 hours to obtain an auxiliary agent.

[0034] Example 2

[0035] To prepare high-strength thermal conductive silicone, the specific steps are as follows:

[0036] Weigh each raw material by weight, premix 15 parts of methyl vinyl silicone rubber (liquid silicone rubber), 24 parts of methyl silicone oil, 6 parts of vinyl silicone oil and 2 parts of hydrogen-based silicone oil (hydrogen content is 0.3wt%), then add 250 parts of aluminum hydroxide and knead. After kneading evenly, add 1 part of the auxiliary agent prepared in Example 1, 0.05 parts of acetic acid-4-ynol, and 0.3 parts of platinum catalyst in sequence, knead again, and cure to obtain high-strength thermally conductive silicone.

[0037] Example 3

[0038] To prepare high-strength thermal conductive silicone, the specific steps are as follows:

[0039] Weigh the raw materials by weight, premix 21 parts of methyl vinyl silicone rubber, 35 parts of methyl silicone oil, 7 parts of vinyl silicone oil and 4 parts of hydrogen-based silicone oil (hydrogen content is 0.3wt%), then add 100 parts of aluminum oxide, 100 parts of magnesium oxide and 100 parts of boron nitride, knead, and after kneading evenly, add 2.5 parts of the auxiliary agent prepared in Example 1, 0.1 parts of 1-ethynyl-1-cyclohexanol and 0.5 parts of platinum catalyst in sequence, knead and cure to obtain high-strength thermally conductive silicone.

[0040] Example 4

[0041] To prepare high-strength thermal conductive silicone, the specific steps are as follows:

[0042] Weigh each raw material by weight, premix 25 parts of methyl vinyl silicone rubber, 40.5 parts of methyl silicone oil, 4.5 parts of vinyl silicone oil and 5 parts of hydrogen-based silicone oil (hydrogen content is 0.3wt%), then add 100 parts of aluminum hydroxide, 50 parts of magnesium oxide, 100 parts of silicon dioxide and 100 parts of boron nitride, knead, and then add 3 parts of the auxiliary agent prepared in Example 1, 0.05 parts of 2-vinyl isopropanol, 0.1 parts of 4-pentyn-1-ol and 0.6 parts of platinum catalyst in sequence after kneading evenly, then knead and cure to obtain high-strength thermally conductive silicone.

[0043] Comparative Example 1

[0044] Prepare thermal conductive silicone, the specific steps are as follows:

[0045] The remaining steps remain unchanged, only the auxiliary agent in Example 4 is removed to prepare the thermal conductive silica gel.

[0046] Comparative Example 2

[0047] Prepare thermal conductive silicone, the specific steps are as follows:

[0048] The remaining steps remained unchanged, except that the auxiliary agent in Example 4 was replaced by 2 parts of antioxidant 1010 and 1 part of ultraviolet absorber UV-0 to prepare thermal conductive silica gel.

[0049] Performance Testing

[0050] The thermally conductive silica gels prepared in Examples 2-4 and Comparative Examples 1-2 were made into corresponding samples according to different standards and subjected to performance tests. The test results are shown in Table 1 below:

[0051] Table 1

[0052]

[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-strength thermally conductive silicone, characterized in that: The invention comprises the following raw materials in parts by weight: 15-25 parts of liquid silicone rubber, 30-45 parts of silicone oil, 2-5 parts of cross-linking agent, 0.05-0.15 parts of inhibitor, 1-3 parts of auxiliary agent, 250-350 parts of thermal conductive filler, and 0.3-0.6 parts of catalyst; Wherein, the auxiliary agent is prepared by the following steps: S1. Add 2,4-dihydroxybenzophenone, pyridine and anhydrous ethanol into a flask under nitrogen protection, add 3-chloropropyltrimethoxysilane after stirring, react at 110° C. for 4 h, cool, concentrate, wash, concentrate again, recrystallize, filter and dry to obtain intermediate 1; S2. Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, glycerol and DMF into a flask under nitrogen protection, add concentrated sulfuric acid after stirring, react at 110° C. for 3 h, cool, add sodium carbonate solution, separate the layers, take the organic phase, dry it, filter it, evaporate it under reduced pressure, purify it by column chromatography, and evaporate it under reduced pressure to obtain intermediate 2; S3. After nitrogen is blown into the flask, add intermediate 2, tetraisopropyl titanate and DMF, stir, add intermediate 1 and DMF, react at 90° C. for 24 h, cool, distill under reduced pressure, wash, and dry to obtain an auxiliary agent.

2. The high-strength thermally conductive silicone according to claim 1, characterized in that: The amount ratio of 2,4-dihydroxybenzophenone, 3-chloropropyltrimethoxysilane, pyridine and anhydrous ethanol in step S1 is 17.1 g: 15.5 mL: 7.8 mL: 180 mL; the amount ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, glycerol, concentrated sulfuric acid and DMF in step S2 is 29.9 g: 3.7 mL: 1.1 mL: 200 mL; the amount ratio of intermediate 1, intermediate 2, tetraisopropyl titanate and DMF in step S3 is 13 g: 18.4 g: 0.026 g: 180 mL.

3. The high-strength thermally conductive silicone according to claim 1, characterized in that: The silicone oil is prepared by mixing methyl silicone oil and vinyl silicone oil in a mass ratio of (4-9):

1.

4. The high-strength thermally conductive silicone according to claim 1, characterized in that: The crosslinking agent is hydrogen-based silicone oil.

5. The high-strength thermally conductive silicone according to claim 1, characterized in that: The inhibitor is one or more of 1-ethynyl-1-cyclohexanol, 2-vinyl isopropanol, 4-pentyn-1-ol, and acetic acid-4-ynol.

6. The high-strength thermally conductive silicone according to claim 1, characterized in that: The thermal conductive filler is one or more of aluminum oxide, aluminum hydroxide, magnesium oxide, silicon dioxide, and boron nitride.

7. The high-strength thermally conductive silicone according to claim 1, characterized in that: The catalyst is a platinum catalyst.

8. The method for preparing high-strength thermally conductive silica gel according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight, premix the liquid silicone rubber, silicone oil and crosslinking agent, add the thermal conductive filler and knead them, add the auxiliary agent, inhibitor and catalyst in sequence after kneading evenly, knead and cure, and obtain high-strength thermal conductive silicone.

Citation Information

Patent Citations

  • Hindered phenol dangled polyurethane damping material and preparation method thereof

    CN102898606A

  • Pre-crosslinked black high-adhesion flame-retardant packaging adhesive film and preparation method thereof

    CN113150721A